(untitled) (BIRDEM Medical Journal, 2021)
Background: Chikungunya is a mosquito-borne viral disease and presentation usually follows 3 phases: acute, sub-acute and chronic. Erratic, relapsing and incapacitating arthritis is the hallmark of chikungunya and many patients go on to develop post-chikungunya arthritis. Bangladesh experienced a major outbreak of chikungunya since April-May of 2017 which created a mass panic among people. The present study aimed to evaluate the course and pattern of musculoskeletal manifestations of patients who had been diagnosed as a case of chikungunya fever Methods: It was a prospective observational study, conducted in Department of Internal Medicine, BIRDEM General Hospital from October, 2017 to August, 2018. Total 100 patients suffering from chikungunya were selected and data were collected by interview using a semi-structured questionnaire and medical records analysis. These patients were followed up after 3 weeks and 3-months of symptom onset and musculoskeletal features were recorded. Results: A total 100 patients were studied and among them female patients were 54%. Mean age of the patients was 49.7 years. Eighty-three patients were managed from outpatient department. All of the patients had history of fever and joint pain at the onset. Among 100 patients, musculoskeletal symptoms resolved in 23 patients within the acute phase and 77% went through sub-acute phase. Twenty six percent patients entered into chronic phase. Conclusion: Study revealed that for one-fourth patients, musculoskeletal manifestations resolved in acute phase, three-fourth patients entered in sub-acute phase and one-fourth patients entered in chronic phase. BIRDEM Med J 2021; 11(3): 166-171